Faktor-Faktor Yang Mempengaruhi Motivasi Mahasiswa Menjadi Enterpreneur Syariah - Ananda Putri; Mellya Embun Baining; Fauzan Ramli (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to determine the influence of independence, environment, creativity and education on students' motivation to become sharia entrepreneurs. Study students at the Faculty of Economics and Islamic Business, Sultan Thaha Saifuddin State Islamic University, Jambi, the subjects of this research are students at the Faculty of Economics and Islamic Business, Sultan Thaha State Islamic University. Saifudin Jambi. Data collection techniques use observation, questionnaires and documentation where the research method used is a quantitative research method that uses primary data and secondary data with a multiple linear regression model. The results of partial testing (t test) of the independence variable and environmental variables do not have a significant effect on students' motivation to become sharia entrepreneurs. while the creativity variable and the education variable have a significant effect on students' motivation to become sharia entrepreneurs. Based on the results of the F test (simultaneous test) it can be concluded that independence, environment, creativity and education simultaneously have a significant effect on students' motivation to become sharia entrepreneurs.